2008
DOI: 10.1183/09031936.00003707
|View full text |Cite
|
Sign up to set email alerts
|

Elevated expression of adenosine A1 receptor in bronchial biopsy specimens from asthmatic subjects

Abstract: Asthmatics, unlike healthy subjects, experience bronchoconstriction in response to inhaled adenosine, and extracellular adenosine concentrations are elevated in the bronchoalveolar lavage fluid and exhaled breath condensate of asthmatic subjects. However, little is known about the location and expression of adenosine receptors in asthmatic airways. The aim of the present study was to investigate the distribution of adenosine A 1 receptors in bronchial biopsy specimens from mildly asthmatic steroid-naïve subjec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
42
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(46 citation statements)
references
References 31 publications
1
42
0
3
Order By: Relevance
“…The use of a selective A 1 antagonist produced a significant reduction of airway hyperresponsiveness in allergic rabbits by blocking these receptors (44). A very recent study reported that the expression of A 1 AR is significantly elevated in airway smooth muscle in asthmatic patients (7). Other than the effects on airway smooth muscle, the A 1 AR has been implicated in increased mucin production in human tracheal cells (36) and in mediating monocyte phagocytosis (49).…”
mentioning
confidence: 99%
“…The use of a selective A 1 antagonist produced a significant reduction of airway hyperresponsiveness in allergic rabbits by blocking these receptors (44). A very recent study reported that the expression of A 1 AR is significantly elevated in airway smooth muscle in asthmatic patients (7). Other than the effects on airway smooth muscle, the A 1 AR has been implicated in increased mucin production in human tracheal cells (36) and in mediating monocyte phagocytosis (49).…”
mentioning
confidence: 99%
“…Обнаружено [1], что в стрессовых условиях, таких как ишемия, сепсис и тяжёлая травма длительное увеличение концентрации внеклеточного аденозина может усугублять течение патологического процесса [2][3][4].…”
Section: Introductionunclassified
“…Studies have demonstrated the synergy between adenosine receptor activation and allergens in inducing mast cell degranulation 3,4 . The involvement of A 1 -ARs have been identified on a number of different human cell types that are important in the pathophysiology of asthma, including human airway epithelial and bronchial smooth muscle cells, lymphocytes, mast cells, neutrophils, monocytes, macrophages, fibroblasts and endothelial cells [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] . Activation of A 1 -ARs subsequently induces the release of mediators and cytokines that lead to airway hyper-reactivity, inflammation and airway remodeling.…”
Section: Introductionmentioning
confidence: 99%